2021
DOI: 10.1016/j.echo.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Functional Versus Organic Mitral Regurgitation After Transcatheter Mitral Valve Repair: Implications from Three-Dimensional Echocardiographic Analysis of Mitral Valve Geometry and Left Ventricular Dilation for a Point of No Return

Abstract: Background: MitraClip implantation has become the standard transcatheter mitral valve repair (TMVR) technique for severe mitral regurgitation (MR). However, approximately one third of patients have poor outcomes, with MR recurrence at follow-up. The aim of this study was to investigate whether quantitative analysis of mitral valve (MV) geometry on three-dimensional (3D) echocardiography can identify geometric parameters associated with the recurrence of severe functional MR (FMR) versus organic MR (OMR) at 6-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Although evidence for mechanisms behind delayed FMR deterioration is limited, several anatomic predictors, including LVEDV, may play a key role. 25,26 This sobering reality contrasts with the excellent 1-and 2-year echocardiographic data from the COAPT trial showing maintained MR reduction over time, although patient-level FMR follow-up has not been published to date. Several studies have reported discharge and 12-month FMR grade but did not perform pairwise comparisons of postprocedural versus 12-month FMR grade, [27][28][29][30] precluding reliable insights on durable effects of TEER on FMR reduction.…”
Section: Discussionmentioning
confidence: 97%
“…Although evidence for mechanisms behind delayed FMR deterioration is limited, several anatomic predictors, including LVEDV, may play a key role. 25,26 This sobering reality contrasts with the excellent 1-and 2-year echocardiographic data from the COAPT trial showing maintained MR reduction over time, although patient-level FMR follow-up has not been published to date. Several studies have reported discharge and 12-month FMR grade but did not perform pairwise comparisons of postprocedural versus 12-month FMR grade, [27][28][29][30] precluding reliable insights on durable effects of TEER on FMR reduction.…”
Section: Discussionmentioning
confidence: 97%
“…Multicenter, randomized clinical TEER trials with standardized follow-up intervals and echocardio-graphic core laboratory-adjudicated outcomes improved our understanding of the timing and mechanisms of recurrent MR associated with this procedure, 62 , 63 notwithstanding limitations of almost universal short-term follow-up periods, 60 , 63 as well as the constant evolution of the transcatheter device arena. National TEER registries only include site-reported, short-term outcomes.…”
Section: Dmr Cardiac Remodeling and Heart Failurementioning
confidence: 99%
“…Patients’ baseline characteristics and several echocardiographic parameters, including mitral valve (MV) features, have been reported to predict the success of TMVR and post‐procedural survival in patients with FMR 2,5,7 . Several parameters assessed by three‐dimensional (3D) transesophageal echocardiography (TEE) have also been shown to be helpful in predicting outcomes after TMVR 8–10 . We aimed to determine the MV leaflet features and 3D‐TEE parameters that affect residual regurgitation after TMVR in patients with FMR.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,7 Several parameters assessed by threedimensional (3D) transesophageal echocardiography (TEE) have also been shown to be helpful in predicting outcomes after TMVR. [8][9][10] We aimed to determine the MV leaflet features and 3D-TEE parameters that affect residual regurgitation after TMVR in patients with FMR.…”
mentioning
confidence: 99%